ANALISIS BIBLIOMETRIK INTEGRASI FAKTOR KEBERLANJUTAN DALAM MODEL FAMA-FRENCH - Maulana, Yasir (UNIVERSITAS DHARMAWANGSA, 2025)
The Fama-French model has long served as a fundamental framework for explaining variations in stock returns through market risk, firm size, and book-to-market ratio factors, later expanded to include profitability and investment components. However, the growing urgency of sustainability issues in the global financial system calls for the adaptation of asset pricing models to reflect environmental, social, and governance (ESG) dimensions. This study aims to map the scientific development of sustainability integration within the Fama–French model using a bibliometric approach. Data were collected from the Scopus database using the keywords “Fama–French” and “Sustainability/ESG” for the 2000–2024 publication period. The analysis was conducted using VOSviewer and Biblioshiny to identify publication trends, author collaboration, influential journals, and thematic clusters. The findings indicate a significant increase in publications since 2016, with dominant themes including sustainable asset pricing, ESG performance, and risk-adjusted returns. Integrating ESG factors enhances the multifactor model by incorporating non-financial risk dimensions that influence long-term returns. This study contributes to strengthening the body of knowledge in sustainable finance and provides direction for future research on developing asset pricing models that are more inclusive, resilient, and responsive to global sustainability challenges.